TEKNIK PCR ITS-RFLP UNTUK SELEKSI ISOLAT JAMUR PADA PENGUJIAN AGEN PENGENDALI HAYATI PADA SERANGAN GANODERMA TANAMAN Acacia mangium - Istiana Prihatini; Farah Aulya Faradilla; Suranto Suranto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2019)
In vivo control activities test of BCA candidate is required to evaluate its effectiveness. This test involved identification of the fungal species that inhabited the experimental plant after inoculation of BCA and pathogen. Identification of inhabitant fungi in the BCA control activity test can be conducted by culturing the fungi on artificial media. Fungal species can be identified based on morphological characters or genetic characters of fungal culture. This study was conducted to determine the potential of PCR ITS-RFLP molecular markers in the initial selection process of fungal isolates before identification based on DNA sequences and to select the enzyme that produce polymorphic PCR ITS RFLP pattern. Three enzymes (DraI, EcoRI and HinfI) were successfully separated 8 fungal cultures used in this study into three groups based on the pattern of PCR ITS DNA, while five other enzymes (BamHI, BclI HaeII, HpaI, and HindIII) were failed to cut the DNA ITS fragments, except for one isolate.